Identification of Nef-HIV-1 domains involved in p22-phox interaction and superoxide production. - Terán- ínge, Guillermo; Montes-Berrueta, Daniela; Valencia-Molina, Juan Camilo; Gabaldon-Figueira, Juan Carlos; Bastidas-Azuaje, Miguel Alejandro; Peterson, Darrell; Berrueta, Lisbeth; Salmen, Siham (Investigación Clínica, 2016)
Abstract. Nef -HIV-1 has been shown to be involved in NADPH complex interaction and superoxide production. The aim of this work was to study the domains involved in the interaction between Nef and p22-phox. Two approaches were used: 1) in silico modelling,to determine the potential binding motifs and design Nef truncated forms and 2) functional assays. The results showed that GFPVT 68-72, FPDW 121-124 and REVLE 179-183 on Nef are critical for p22-phox (RPQIG 142-146 and PGGP 181-184) docking. However, only the region containing FPDW 121-124 on Nef is able to induce superoxide production. Understanding the molecular mechanisms involved in generating oxidative stress during HIV infection, is critical for therapeutic intervention, in order to minimize viral replication and dissemination.